Громадсько-просвітницька діяльність Арсена Річинського на Волині у 20–30-х рр. ХХ ст. - Петрович, Валентина; Петрович, Ігор; Притулюк, Василь; Petrovych, Valentina; Petrovych, Ihor; Pritulyk, Vasil (My University, 2016)
У статті висвітлено громадсько-просвітницьку діяльність Арсена Річинського на Волині у 20–30-х рр. ХХ ст., спрямовану на підтримку національно-церковного руху в Православній церкві. Розкрито роль Арсена Річинського в процесі українізації церковно-релігійного устрою, у просвітянському русі та боротьбі за утвердження й збереження духовної, релігійної, національної самобутності українців Волині.The article highlights public and educational activity of Arsen Richinskiy on the territory of Volyn in 20-30-ies of the 20th century aimed at the support of the national and religious movement within Orthodox Church. The authors analyzed path of life and career of Arsen Richinskiy - one of the leading characters of the religious movement for the ukrainization of the Orthodox Church on the territory of Volyn during interbellum period. The role of Arsen Richinskiy in the establishment of the independent Ukrainian Orthodoxy and its rule of the council was described.
Public and Educational Activity of Arsen Richinskiy on the Territory of Volyn in 20-30-ies of the 20th Century
Keywords: Арсен Річинський; громадсько-релігійне життя; Просвіта; Arsen Richinskiy; public and religious life; Prosvita; ukrainization; church convention; Orthodox Church